iso‐Fatty Acid Metabolism in Caenorhabditis elegans’ Ceramide Biosynthesis - Rivera Sánchez, Rocío; Bandi, Siva; Schlemper-Scheidt, Marie-Désirée; Laaroussi, Hanna; William Fox, Bennett; Ishida, Yojiro; Glauser, Gaëtan; Sutour, Sylvain; Von Reuss, Stephan (Wiley, 2023)
Ceramide biosynthesis and its connection to iso-fatty acid metabolism in the model organism Caenorhabditis elegans was investigated using a combination of reverse genetics and comparative ESI-(+)-HR-MSe ceramide profiling along with incorporation experiments with bacterial mutants specifically enriched with isotopically labeled branched-chain amino acids or branched-chain fatty acids. Incorporation of a L-leucine-derived isovalerate unit into the conserved d17: 1iso sphingosine building block proceeds through elo-5 dependent chain elongation and depends on peroxisomal β-oxidation by the 3-ketoacyl-CoA thiolase daf-22, although ceramide profiles of N2 wildtype and daf-22(ok693) are indistinguishable. Biosynthesis of the homologous N-isoacyl moieties also depends on L-leucine and isovalerate chain elongation but proceeds independently of elo-5 and daf-22. Biosynthesis of the dominating N-docosanoyl moiety depends on elo-3-catalyzed chain elongation of bacteria-derived palmitic acid, whereas the N-tetracosanoyl moiety is derived from de novo lipogenesis.